Certain Subclasses of k - Uniformly Starlike and Convex Functions Defined by Convolution with Varying Arguments of Coefficients - A. A. Hussain , A. O. Mostafa; M. K. Aouf (Journal of Pure & Applied Sciences, 2019)
In this paper we introduce and study the subclass , AU0x(f,g,a,b,k) which represent the -uniformly analytic functions of order ? with varying argument of coefficients. Moreover, we give coefficient estimates, growth distortion bounds and radii of starlikeness and convexity.